From tradition to trait: stay-green alleles in Sudanese Feterita unlock pathways to climate-resilient sorghum - Elsafy, Mohammed; Abdalla, Aisha Abdalhady Ahmed; Abdo, Shama; Ahmed, Alaa; Novakazi, Fluturë; Hovmalm, Helena Persson; Johansson, Eva; Ortiz, Rodomiro; Rahmatov, Mahbubjon; Abdelhalim, Tilal (Frontiers in Plant Science, 2026)
IntroductionSorghum is a vital crop for food and nutritional security in drought-prone regions. However, the genetic potential of Sudanese Feterita landraces for stay-green (Stg) traits remains largely unexplored. MethodsThis study evaluated 133 Feterita genotypes using an integrated approach combining field phenotyping with KASP genotyping targeting the Stg3A and Stg3B QTLs. The genotypes were assessed during the 2022 season at the Gezira Research Station using an augmented design, and 14 morphological and agronomic traits were recorded for each genotype. Results and DiscussionSubstantial phenotypic variation was observed, with particularly high coefficients of variation for flowering stalks per plant (81.25%), senescence (49.09%), and grain number per panicle (43.33%). Genetic diversity analysis revealed moderate marker informativeness (GD = 0.407, I = 0.293, and PIC = 0.592). The AMOVA indicated weak population differentiation (Fst = 0.014), with 94% of the variation occurring within populations and substantial gene flow (Nm = 6.117). Pairwise Fst identified West Darfur and Blue Nile as genetically distinct, whereas Kordofan, White Nile, and Al-Gezira formed a cohesive cluster. Significant marker-trait associations were detected, including snpSB0054 (SGR1) with plant height and flowering time, snpSB0072 with panicle length, and snpSB0101 (SGR3) with grain number and seed yield. These findings highlight Feterita as a valuable reservoir of functional Stg alleles that influence senescence dynamics and drought-related yield traits. This study provides the first targeted characterization of stay-green alleles in Sudanese Feterita and lays the foundation for exploiting this germplasm in marker-assisted breeding to develop climate-resilient sorghum varieties in the future.